Sources of roughage and milo for finishing steers - K.K. Bolsen; G. Fink; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1975)
We used 75 yearling steers in a 92-day trial to evaluate three sources of roughage: (1) chopped prairie hay; (2) milo stover silage; and (3) milo stover pellets; and five milo treatments: (1) dry, 85.5% dry matter (DM); (2) field harvested, high moisture (F-HM), 72.6% DM, ensiled in an O2-limiting structure; (3) F-HM, 79.5% DM, treated with 1.75% ammonium isobutyra1te on a wet basis and stored in a metal bin; (4) F-HM, 73.6% DM, rolled and ensiled in a 10 ft. x 50 ft. concrete stave silo; and (5) harvested at 85.5% DM and reconstituted to 73.3% DM, rolled and ensiled in a 10 ft. x 50 ft. concrete stave silo. Neither performance or carcass characteristic differences could be attributed to source of roughage when it was fed at 15% of the ration dry matter, which indicates that milo stover can be effectively used in finishing rations. Steers fed high-moisture milo treated with AIB or stored in an O2 -limiting structure performed similarly and gained faster (P<.05) and more efficiently (P<.05) than steers fed dry milo.
Keywords: Cattlemen& #x27; s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Roughage; Milo; Finishing steers